Separation and identification of many volatile oil compounds and phenolic compounds from the seeds of Ammi visnaga (L.) growing in Iraq - Al-Zaidi, Yusra. M.; Khorsheed, Ayad C. (Journal of Kerbala for Agricultural Sciences, 2021)
The current research was contained the separation and identification of Many volatile oil compounds from the seeds of Ammi visnaga (L.), using converted Clevenger apparatus for night oil and the results were confirmed by using GLC technique and identified of many volatile oil compounds as following: (α- pinene, Linalool, Sabinin, Limonine, Terpinen and Myrcene, and these componds were appeared in the normal water extract and zamzam water extract and also in the pet- ether extract (A1) and in chloroform (A2) and also in Acetone extract (A3) and the higher concentration of these compounds was found in the zamzam water extract. We were obtained many of plant extracts from the seeds of Ammi visnaga (L.), using soxhlet apparatus with following solvents as following: pet. Ether (A1), Chloroform (A2), Acetone (A3), Ethanol (A4), as well as the hot aqueous extract (A5). Moreover, the acid hydrolysis was carried out to get some free phenolic compounds from the (A3, A4 and A5) extracts and identification was investigated by using HPLC technique to appear the following phenolic compounds; (Coumarin, Apignin, Kaempferol, Caffeic acid, Rutin, Quercetin, Visnagin and Ferulic acid). All the phenolic compounds were appeared in the mentioned three extracts except of ferulic acid that was not appear in Acetone extract (A3) and the highest concentration of these compounds was in the hot aqueous extract (A5).